An investigation on physical, mechanical and microstructural properties of electricity-based cured GBFS-FA geopolymer - Aygun, Beyza Fahriye; Uysal, Mucteba; Bilir, Turhan; Cosgun, Turgay; Dilbas, Hasan (ELSEVIER SCI LTD, 2025)
This paper aimed to investigate and develop curing process of geopolymer as a building material of the future. As well-known, the geopolymer may require heat while hardening and gaining strength. Application of heat treatment to the geopolymer on-site with heat sources are solutions, but it can be said that it is one of the most difficult processes of geopolymer. Thus, on-site electricity curing has been developed to overcome the difficulties in geopolymer curing. The developed curing process depended on application of AC voltage (10 V, 20 V, and 30 V) and the electrical resistance of geopolymer ensured a heat on geopolymer while curing process. In this experimental study, different NaOH and different GBFS/FA ratios were employed to seek the best solution. Also, the electrical resistance/conductivity of geopolymer was regulated with the addition of carbon fiber (CF), steel fiber (ST), waste wire erosion (WWE) (0.25 %, 0.50 %, and 0.75 %), and carbon black (CB) (1 %, 2 % and 3 %). Compressive strength (CS), flexural strength (FS), ultrasound pulse velocity (UPV), water absorption, void ratio, and unit weight were investigated parameters of geopolymer and were used to determine the best geopolymer mixtures. The internal and surface temperatures of geopolymer can be regulated by electricity-based thermal curing and it ensured a capability to set the optimum temperature on geopolymer. 20 V applications had the best efficiency in activating the geopolymerization reaction and the compressive strength positively affected, resulting the highest compressive strength as 78.02 MPa for SFA05WWE. Electricity-based thermal curing had a significant potential to surpass on-field-challenges in curing process of geopolymer and to obtain desired strength grade in not only indoor but also outdoor engineering applications.
Keywords: Thermal curing; Geopolymer mortars; Fibers; Physical properties; Mechanical properties; STRENGTH DEVELOPMENT; CARBON-FIBER; ASH; CONCRETE; Construction & Building Technology; Engineering; Materials Science